2006
DOI: 10.1093/jac/dkl387
|View full text |Cite
|
Sign up to set email alerts
|

Testing the mutant selection window hypothesis with Staphylococcus aureus exposed to daptomycin and vancomycin in an in vitro dynamic model

Abstract: These findings support the MSW hypothesis and suggest comparable antistaphylococcal effects of clinically achievable AUC24/MIC90s of daptomycin and vancomycin but slightly better prevention against the selection of resistant S. aureus by daptomycin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
55
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(67 citation statements)
references
References 27 publications
11
55
1
Order By: Relevance
“…Similar observations were obtained with S. pneumoniae [32] and by additional experments with S. aureus [26,33,34]. The principle has also been extended to S. aureus for vancomycin and daptomycin [35]. Longer exposure inside the selection window should allow greater mutant amplification [36].…”
Section: Dynamic Models and The Window Hypothesismentioning
confidence: 54%
See 2 more Smart Citations
“…Similar observations were obtained with S. pneumoniae [32] and by additional experments with S. aureus [26,33,34]. The principle has also been extended to S. aureus for vancomycin and daptomycin [35]. Longer exposure inside the selection window should allow greater mutant amplification [36].…”
Section: Dynamic Models and The Window Hypothesismentioning
confidence: 54%
“…value or the AUC 24 /MPC value is more predictive with individual isolates when measured in vitro [35,39].…”
Section: Dynamic Models and The Window Hypothesismentioning
confidence: 96%
See 1 more Smart Citation
“…From a practical perspective, to maintain drug levels above MPC is often more stringent than necessary and increases risk of toxicity. However, the MPC‐based PK/PD measurement, AUC 24 /MPC, has been tested to be more accurate than AUC 24 /MIC in predicting resistance occurrence (Firsov et al, 2006; Olofsson et al, 2006; Drlica and Zhao, 2007), and in vivo experiments also prove the usefulness to control the frequency of resistant mutant development by maintaining drug levels above MPC for certain time of period (Croisier et al, 2004; Etienne et al, 2004). Given the high plasma drug exposure potential and wide safety margin of CD101, and the fact that CD101 and MCF have the same MPC value suggests a possible advantage of CD101 in preventing resistance to currently approved echinocandin drugs.…”
Section: Discussionmentioning
confidence: 99%
“…25 Testing involving S. aureus for vancomycin and using in vitro dynamic models revealed that mutants are selectively amplified when concentrations are between the MIC and the MPC. 26 Stepwise accumulation of drug resistance on the MSW was examined in fluoroquinolone resistance of Haemophilus influenzae. 27 Observations strongly suggested that these vancomycin-intermediate S. aureus isolates represent the progeny of a single MRSA strain that emerged in vivo under the selective pressure of vancomycin therapy.…”
Section: Discussionmentioning
confidence: 99%